Self-Assembly Investigations of Sulfonated Poly(methyl methacrylate-block-styrene) Diblock Copolymer Thin Films - Claudia Piñón-Balderrama; César Leyva-Porras; Roberto Olayo-Valles; Javier Revilla-Vázquez; Ulrich S. Schubert; Carlos Guerrero-Sanchez; José Bonilla-Cruz (Advances in Polymer Technology)
Poly(methyl methacrylate-block-styrene) block copolymers (BCs) of low dispersity were selectively sulfonated on the styrenic segment. Several combinations of degree of polymerization and volume fraction of each block were investigated to access different self-assembled morphologies. Thin films of the sulfonated block copolymers were prepared by spin-coating and exposed to solvent vapor (SVA) or thermal annealing (TA) to reach equilibrium morphologies. Atomic force microscopy (AFM) was employed for characterizing the films, which exhibited a variety of nanometric equilibrium and nonequilibrium morphologies. Highly sulfonated samples revealed the formation of a honeycomb-like morphology obtained in solution rather than by the self-assembly of the BC in the solid state. The described morphologies may be employed in applications such as templates for nanomanufacturing and as cover and binder of catalytic particles in fuel cells.